Human and experimental evidence supporting a role for osteopontin in alcoholic hepatitis. Issue 5 (19th August 2013) - Morales‐Ibanez, Oriol; Domínguez, Marlene; Ki, Sung H.; Marcos, Miguel; Chaves, Javier F.; Nguyen‐Khac, Eric; Houchi, Hakim; Affò, Silvia; Sancho‐Bru, Pau; Altamirano, José; Michelena, Javier; García‐Pagán, Juan Carlos; et al.
<x xml:space="preserve">Abstract</x> We identified, in the transcriptome analysis of patients with alcoholic hepatitis (AH), osteopontin (OPN) as one of the most up‐regulated genes. Here, we used a translational approach to investigate its pathogenic role. OPN hepatic gene expression was quantified in patients with AH and other liver diseases. OPN protein expression and processing were assessed by immmunohistochemistry, western blotting and enzyme‐linked immunosorbent assay. OPN gene polymorphisms were evaluated in patients with alcoholic liver disease. The role of OPN was evaluated in OPN−/− mice with alcohol‐induced liver injury. OPN biological actions were studied in human hepatic stellate cells (HSCs) and in precision‐cut liver slices. Hepatic expression and serum levels of OPN were markedly increased in AH, compared to normal livers and other types of chronic liver diseases, and correlated with short‐term survival. Serum levels of OPN also correlated with hepatic expression and disease severity. OPN was mainly expressed in areas with inflammation and fibrosis. Two proteases that process OPN (thrombin and matrix metalloproteinase 7) and cleaved OPN were increased in livers with AH. Patients with AH had a tendency of a lower frequency of the CC genotype of the +1239C single‐nucleotide polymorphism of the OPN gene, compared to patients with alcohol abuse without liver disease. Importantly, OPN−/− mice were protected against alcohol‐induced liver injury and showed decreased expression of inflammatory cytokines. Finally, OPN was induced by lipopolysaccharide and stimulated inflammatory actions in HSCs. Conclusion: Human and experimental data suggest a role for OPN in the pathogenesis of AH. Further studies should evaluate OPN as a potential therapeutic target. (Hepatology 2013;58:1742–1756)